2021
DOI: 10.1021/acsenergylett.1c02332
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Interface for High-Rate and Long-Durable Garnet-Type Solid Electrolyte in Lithium Metal Batteries

Abstract: Lithium dendrite growth in solid electrolytes is one of the major obstacles to the commercialization of solid-state batteries based on garnet-type solid electrolytes. Herein, we propose a strategy that can simultaneously resolve both the interface and electronic conductivity issues via a simple one-step procedure that provides multilayer protection at low temperature. We take advantage of the facile chemical conversion reaction, showing the wet-coated SnF 2 particles on the solid electrolyte effectively produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 43 publications
0
59
0
Order By: Relevance
“…In addition, to measure the electronic conductivity, the DC polarization was conducted with an applied voltage of 1 V for 3000 s. As presented in Figure S5 (Supporting Information), it was verified that Na 2 TiFeF 7 delivered the high electronic conductivity of ≈9.75 × 10 −5 S cm −1 , which is much larger than the solid‐electrolytes based on low electronic conductivity such as Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 (≈1.57 × 10 −9 S cm −1 ), 2LiCl−GaF 3 (≈4 × 10 −9 S cm −1 ), etc. [ 30,31 ] As shown in Figure 3c, ≈71% of the initial specific capacity was retained after 600 cycles at 1C, with a high coulombic efficiency of above 99%. In addition, it was reported that the undesirable electrolyte decomposition can be occurred after numerous cycles at the high voltage region.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, to measure the electronic conductivity, the DC polarization was conducted with an applied voltage of 1 V for 3000 s. As presented in Figure S5 (Supporting Information), it was verified that Na 2 TiFeF 7 delivered the high electronic conductivity of ≈9.75 × 10 −5 S cm −1 , which is much larger than the solid‐electrolytes based on low electronic conductivity such as Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 (≈1.57 × 10 −9 S cm −1 ), 2LiCl−GaF 3 (≈4 × 10 −9 S cm −1 ), etc. [ 30,31 ] As shown in Figure 3c, ≈71% of the initial specific capacity was retained after 600 cycles at 1C, with a high coulombic efficiency of above 99%. In addition, it was reported that the undesirable electrolyte decomposition can be occurred after numerous cycles at the high voltage region.…”
Section: Resultsmentioning
confidence: 95%
“…In this regard, previous efforts have been placed in enhancing the interfacial homogeneity by removing impurities at the interface ( 17 , 18 ) or improving the wettability of lithium metal by inserting lithiophilic interlayers ( 19 25 ). Various lithiophilic interlayers were thus explored such as materials that can alloy with lithium (e.g., Ge or Ga) ( 20 , 24 ) or have conversion reactions with lithium metal [e.g., Zn(NO 3 ) 2 or SnF 2 ] ( 19 , 21 ), which could notably improve the performance. Nevertheless, the short circuits caused by lithium dendrites still happen after prolonged cycling or when operated at a moderately high current density.…”
Section: Introductionmentioning
confidence: 99%
“…It has been theoretically and experimentally demonstrated that the elastic modulus at the grain boundaries in the solid electrolyte is ~50% less than that of the grain, leading to the intergranular crack and lithium dendritic growth along the grain boundaries/interconnected pores in the pellets (15,16). In this regard, previous efforts have been placed in enhancing the interfacial homogeneity by removing impurities at the interface (17,18) or improving the wettability of lithium metal by inserting lithiophilic interlayers (19)(20)(21)(22)(23)(24)(25). Various lithiophilic interlayers were thus explored such as materials that can alloy with lithium (e.g., Ge or Ga) (20,24) or have conversion reactions with lithium metal [e.g., Zn(NO 3 ) 2 or SnF 2 ] (19, 21), which could notably improve the performance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] However, the demanding preparation process (high‐temperature, chemical pretreatment) and moisture‐proof storage condition would compromise the potential scalability of the strategy. [ 27–30 ] To better afford the fundamental insights for the practical Li metal battery (LMB) designs (for instance the cathode/anode pairing, formation protocols, irreversible capacity origin of the cell model), additionally, the in‐depth theoretical elucidation and real‐time phase tracking of the alloy transition were urgently required, yet the associating studies of which remained scarce thus far.…”
Section: Introductionmentioning
confidence: 99%